Efisiensi Penggunaan Faktor Produksi Produksi Jagung Hibrida di Desa Sugih Waras Kecamatan Muara Sugihan Kabupaten Banyuasin - Amar, Amar; Iskandar, Sutarmo; Kurniawan, Rahmat (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2017)
ABSTRACTThis study aims to determine To analyze the effect and efficiency of the use of factors of production such as land, labor, seed, fertilizer Urea, SP36, KCl fertilizers and herbicides Gramaxone on hybrid corn production. in the Sugih Waras village Muara Sugihan District Banyuasin Regency. The method used is the method of a survey of corn growers in the Sugih Waras village Muara Sugihan District Banyuasin Regency. Sampling method is done using a random method (simple random sampling) using the formula Slovin. The number of members of the population of hybrid corn farmer in the village of 168 on the Sugih Waras then the amount calculated into the formula Slovin with a confidence level of 85%, 85% confident that the true and the research results with significance level of 0.15, then a sample of the entire population of hybrid maize farmers which can be taken are 35 farmers. Data processing method is the method of interview data collected in this study included primary data and secondary data. Primary data obtained from respondents through direct interviews and field observations accompanied by a list of questions has been provided while secondary data obtained from the competent institutions or agencies associated with this research. Data were processed using mathematical models and presented in tabular form. The results showed that the factors of production labor, urea, fertilizers and herbicides Gramaxone SP36 no significant effect on the production of hybrid corn. While the seeds, area of land and fertilizer KCl significant effect on the production of hybrid corn. Based on the level of inefficiency of production factors such as labor, land, urea and herbicides Gramaxone inefficient that need to be reduced in order to achieve an efficient level. While the factors of production seed, fertilizer KCl, and SP36 has not been so efficient that need to be added to reach the level of inefficiency.